975 Geospatial analysis of sports and leisure injury hospitalisations in Victoria, Australia. (1st September 2016) - Singh, Himalaya; Fortington, Lauren V; Thompson, Helen; Eime, Rochelle; Finch, Caroline
Abstract : Background: Sports injuries are identified as a major public health problem in Australia and around the world. Sports injury prevention strategies and policy development relies on information about when, where, to whom and how sports injuries occur at a population level. The aim of this research is to investigate the geographical distribution of sports and leisure injures and to identify populations who are at greatest risk of injury. Methods: Data on sports and leisure injury hospitalisations were obtained from the Victorian Injury Surveillance Unit for the years 2005–2011, inclusive. Population-standardised sports and leisure injury hospitalisation rates were calculated for each Local Government Area (LGA). The geographical distribution was investigated using Global Moran's I statistics. Gi* statistics were used to identify statistically significant clustering of high and low values of hospitalisation rates, both overall and for specific activity groups. Results: Mapping by LGA showed a spatial variability in the distribution of injury hospitalisation rates. The Global Moran's I value suggested that hospitalisation rates in Victoria by LGA were spatially clustered. The Gi* statistics showed a statistically significant clustering of high values for overall hospitalisation rates in the south-western region of Victoria. Similarly, clustering of high values for team ball sports and wheeled motor sports were identified in the western and south-east regions of Victoria, respectively. Conclusions: This study demonstrates that geospatial analysis can be used for better understanding of the population at risk of sport and leisure injury. Findings suggest that priority geographical areas for sports injury prevention can differ depending on the type of sporting activity. These findings will provide a strong evidence base for the strategic planning, development and delivery of sports and leisure injury prevention programs.